Indian Commercialization of Microfinance: a Study of the Emperor’S Apparel: The Evolution and Commercialization of Microfinance in India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Longbeen discussed as an innovation to address poverty issues, microfinance is nowbeing viewed as the next big investment opportunity. The language ofmicrofinance has undergone a fundamental change in the two decades of itsevolution. As some large microfinance institutions (MFIs) hit the capitalmarket, we examine the origins of these MFIs, their transformation processes,and the overall trajectory of the governance processes.